Identity contestation in Malaysia: a comparative commentary on ‘Malayness’ and ‘Chineseness’ - Shamsul A.B., (Universiti Kebangsaan Malaysia, 1999)
The discourse on ethnic identity is a modern phenomenon. It came along with colonialism, in particular the construction of ‘colonial knowledge’ necessary for purposes of colonial ru,e. The creation of a ‘plural society’ in British Malaya provided the ‘epistemological basis and space’ not only for discourse on ethnic identities but also the assification of ethnic categories into lived reality, be it in the ‘authority-defined’ context as well as the ‘everyday defined’ context. This essay traces the historical trajectory of the construction of Malaysia’s two major ethnic groups, namely, Malay and Chinese, as well as what constitutes “Malayness’ and ‘Chineseness’. It also offers a brief comparative commentary on the latter.